CHALLENGES AND EFFECTS OF POOR RECRUITMENT AND SELECTION PROCESS IN NIGERIAN WORKPLACE - Shulammite Oghenenyerhowvo OMOGBIYA (Indonesian Journal of Digital Business, 2023)
In this study, recruitment and selection procedures in Nigerian organizations were examined. In order to accomplish this, literature on recruitment and selection practices, contemporary trends in recruitment and selection at the workplace in Nigeria, problems and consequences of poor recruitment and selection practices, as well as management strategies for recruitment and selection at the Nigerian workplace, was reviewed. For the purpose of developing a strong justification for the discourse, this study made use of the Human Capital Theory and Resource Based View (RBV) Theory. As a result, this study came to the conclusion that finding the right employee for the right job is essential for organizational success. In order to have a round peg in a round hole, it is advised that organizations in Nigeria constantly check that their recruitment and selection criteria are valid and in line with international best practices. This recommendation includes, among other things that all employers of labor in Nigeria, whether they are public or private, should make sure that qualified human resources experts are in charge of the recruitment and selection process.